Copper(II) bromide as efficient catalyst for silyl- to bisarylmethyl ethers interconversion (transprotection) - Specklin, Simon; Gallier, Florian; RofiaMezaache; Hassina Harkat; Yénimégué Albert Dembelé; Jean-Marc Weibel; Aurélien Blanc; Patrick Pale (Tetrahedron Letters, 2011)
Primary and secondary silylated alcohols are easily converted to bis(methoxyphenyl)methyl (BMPM) ethers in good yields using CuBr2 as catalyst in acetonitrile at room temperature. Various other protecting groups are compatible with this mild and convenient process. Graphical abstract Primary and secondary silylated alcohols are easily and rapidly converted to bis(methoxyphenyl)methyl (BMPM) ethers in good yields using CuBr2 as catalyst in acetonitrile at room temperature. Various other protecting groups are compatible with this mild and convenient process. <figure id="f0025"> </figure>
Keywords: Alcohol; Bis(methoxyphenyl)methyl; Copper; Protecting group; Silyl; Transprotection